A multi-model multi-objective robust damping control of GCSC for hybrid power system with offshore/onshore wind farm. (May 2023) - Sadiq, Rehan; Wang, Zhen; Chung, C.Y.
Highlights: Proposing a multi-model robust dynamic output feedback damping controller for the GCSC. Investigating a two-step LMI approach for solving BMI optimization problem. A multi-objective H 2 / H ∞ synthesis with regional pole-placement. Power system operational uncertainties considering variations in operating conditions are represented as multi-model. Abstract: In the recent decade, the power network has experienced a remarkable energy transition due to the large-scale integration of wind energy resources, especially converter-interfaced modern wind turbines. The increasing/decreasing wind penetration, on the other hand, unexpectedly affects the low frequency oscillations of the modern power grid. In this context, the proposed work adopts a multi-model multi-objective robust control framework to design a supplementary damping controller for the gate-controlled series capacitor (GCSC) to stabilize the hybrid power system with a permanent magnet synchronous generator (PMSG)-based off-shore wind farm (OSWF) and a doubly-fed induction generator (DFIG)-based onshore wind farm (ONWF). A bilinear matrix inequality (BMI) optimization problem, formulated as multi-objective synthesis considering H 2 / H ∞ performance along with pre-defined pole placement, is presented for the GCSC control design, which is solved by a two-step linear matrix inequality (LMI) approach. In addition, all LMI constraints are constructed based on the multi-model control framework to incorporate multiple operating conditions. Afterward, the significant improvement in the damping characteristics of the closed-loop system, covering a wide operating range, is confirmed using eigenvalue analysis. The effectiveness of the scheme is validated using two case studies based on the hybrid power system, subject to various disturbances and uncertainties. The simulation results show the robustness and higher damping performance of the proposed multi-model strategy, compared to a conventional and a robust damping controller, for mitigating power system oscillations alongside voltage fluctuations of the wind farms.